A Novel Immobilized Bacterial Consortium Bioaugmented in a Bioreactor For Sustainable Wastewater Treatment - Tithi Mehrotra; Abhinav Srivastava; R. Pragadeeshwara Rao; Rachana Singh (Journal of Pure and Applied Microbiology, 2019)
The study was undertaken to illustrate the degradation of domestic wastewater collected from two scales of sewage treatment plants, treated in a continuous laboratory-scale bioreactor under aerobic conditions using a synthetically developed consortium comprising of three highly efficient bacteria. The objective of the present work was also to design and optimize the bioreactor functioning varying its operational parameters, viz. flow rate, hydraulic retention time, dilution rate and residence time. After 48 hours of treatment, approximately 5L of domestic water was successfully treated with all the major wastewater parameters eventually lying within the permissible limits given by CPCB/WHO.